Pyramid algorithms a dynamic programming approach to curves and surfaces for geometric modeling - Goldman, Ron, 1947- (San Francisco, Calif. : Morgan Kaufmann, 2003)
Pyramid Algorithms presents a unique approach to understanding, analyzing, and computing the most common polynomial and spline curve and surface schemes used in computer-aided geometric design, employing a dynamic programming method based on recursive pyramids. The recursive pyramid approach offers the distinct advantage of revealing the entire structure of algorithms, as well as relationships between them, at a glance. This book-the only one built around this approach-is certain to change the way you think about CAGD and the way you perform it, and all it requires is a basic background in calculus and linear algebra, and simple programming skills. * Written by one of the world's most eminent CAGD researchers * Designed for use as both a professional reference and a textbook, and addressed to computer scientists, engineers, mathematicians, theoreticians, and students alike * Includes chapters on Bezier curves and surfaces, B-splines, blossoming, and multi-sided Bezier patches * Relies on an easily understood notation, and concludes each section with both practical and theoretical exercises that enhance and elaborate upon the discussion in the text * Foreword by Professor Helmut Pottmann, Vienna University of Technology.
Introduction : foundations -- Lagrange interpolation and Neville's algorithm -- Hermite interpolation and the extended Neville algorithm -- Newton interpolation and difference triangles -- Bezier approximation and Pascal's Triangle -- Blossoming -- B-spline approximation and the de Boor algorithm -- Pyramid algorithms for multisided Bezier patches.
Keywords: Recursive functions -- Data processing; Geometrical drawing -- Data processing; Electronic books